DKA-induced Brugada phenocopy mimicking STEMI. Issue 2 (26th May 2018) - Abrahim, Christian; Maharaj, Satish
Abstract : Case presentation: A 47-year-old Caucasian woman with type 1 diabetes presented with epigastric pain and vomiting. She had not been adherent with her diet and insulin therapy for the past 3 weeks. She never had a personal or family history of arrhythmia-related symptoms, ventricular tachycardia or fibrillation (VT/VF) or premature sudden cardiac death (SCD). Examination revealed dry mucosa, tachycardia and epigastric tenderness to palpation. Her ECG showed ST elevations (V1–V3) with associated T wave inversions (figure 1A ). A baseline ECG 1 year ago had no abnormalities. Serial troponin I and T were negative, but Creatinine Kinase MB (CKMB) was elevated. Her biochemistry test showed sodium of 118 mM, potassium of 6.7 mM, bicarbonate of 4 mM, anion gap of 40, glucose of 985 mM and beta hydroxyl-butyrate of >45.0 mg/dL. Cardiac catheterisation revealed normal anatomy with all vessels widely patent; left ventricular end diastolic pressure (LVEDP) was 1 mm Hg. With treatment, diabetic ketoacidosis (DKA) resolved after 8 hours and repeat ECG showed all changes had resolved (figure 1B ). She was monitored on telemetry without any VT/VF episodes. Serial ECGs were done with resolution of changes. She had no positive studies for inducible VT. The rest of her admission was uneventful. Question: Which of the following is the best next step in managing this patient? Quinidine therapy. Implantable cardioverter-defibrillator (ICD) placement. SCN5A gene mutation testing. Observation without therapy.